Calprotectin as a diagnostic marker for sepsis: A meta-analysis - Gao, Rong-Yue; Jia, Hui-Miao; Han, Yu-Zhen; Qian, Ben-Shu; You, Pan; Zhang, Xiao-Ke; Li, Wen-Xiong; Huang, Li-Feng (Frontiers in Cellular and Infection Microbiology, 2022)
Introduction Sepsis is a life-threatening condition, and biomarkers are needed to diagnose sepsis fast and accurately. We aimed to perform this meta-analysis to investigate the diagnostic value of calprotectin on sepsis in critically ill patients. Methods The investigators searched MEDLINE, Embase, Web of Science and Cochrane Library. Studies were included if they assessed the diagnostic accuracy of serum calprotectin for sepsis in intensive care unit (ICU). We estimated its diagnostic value and explored the source of heterogeneity. The bivariate model and the hierarchical summary receiver operating characteristic (HSROC) curve were used in the meta-analysis. Results Six records assessing 821 patients were included in this meta-analysis. The pooled sensitivity, specificity, positive likelihood ratio (PLR), and diagnostic odds ratio (DOR) were separately as 0.77, 0.85, 5.20, 0.27, respectively. The Fagan's nomogram showed post‐test probabilities of 91% and 35% for positive and negative outcomes, respectively. Subgroup analysis indicated that sepsis definition could be a possible source of heterogeneity, but there’s no sufficient data to investigate sepsis-3 definition. Sensitivity analysis suggested that two studies could affect the stability of pooled results. Conclusion On the basis of our meta-analysis, calprotectin is a helpful marker for early diagnosis of sepsis on ICU admission.